Soft red winter wheat 'GA 051207‐14E53': Adapted cultivar to Georgia and the U.S. Southeast region. Issue 1 (11th February 2021) - Mergoum, Mohamed; Johnson, Jerry W.; Buck, James W.; Sutton, Steve; Lopez, Benjamin; Bland, Daniel; Chen, Z.; Buntin, G.D.; Mailhot, Daniel J.; Babar, Md A.; Mason, Richard E.; Harrison, Stephen A.; et al.
Abstract: Soft red winter wheat (SRWW) ( Triticum aestivum L.) is a major crop in Georgia and the U.S. Southeast (SE) region. Hence, new cultivars with high yield potential, high resistance levels to predominant pests, and adequate quality parameters are required to capture and maximize regional market values. Therefore, the University of Georgia SRWW breeding program in collaboration with the SUNGRAINS breeding programs, aims to develop and release SRWW cultivars adapted to Georgia and the SE wheat region with high yield, quality, and pest resistance. 'GA 051207‐14E53' SRWW (Reg. no. CV‐1168, PI 689518) was developed and released by the University of Georgia and licensed to AGSouth Genetics Company in 2017 under the name AGS 3040. GA 051207‐14E53 is well adapted to Georgia and the SE region. It has high yield and high resistance to leaf rust, stripe rust, and Soil‐borne wheat mosaic virus . It has medium resistance to powdery mildew and to biotypes C and O of Hessian fly and is resistant to biotypes B and L. GA 051207‐14E53 has good Fusarium head blight resistance. GA 051207‐14E53 possesses H9, Sbm1, and the 2NS:2AS alien introgression from Aegilops ventricosa Tausch, having the Yr17/Lr37/Sr38 genes that protect it against these pests. Grain volume weight and milling and baking qualities of GA 051207‐14E53 are good and meet the SRWW grade standards. Core Ideas: GA 051207‐14E53 is a SRWW wheat cultivar adapted to the U.S. Southeast. GA 051207‐14E53 is resistant to leaf and stripe rusts. GA 051207‐14E53 has good resistance to scab (FHB), Hessian fly, and powdery mildew. GA 051207‐14E53 has good milling and baking qualities.